Tolerability of High-Dose Venlafaxine After Switch From Escitalopram in Nonresponding Patients With Major Depressive Disorder. Issue 1 (January 2021) - Engelmann, Jan; Wagner, Stefanie; Solheid, Andreas; Herzog, David P.; Dreimüller, Nadine; Müller, Marianne B.; Tadić, André; Hiemke, Christoph; Lieb, Klaus
Abstract: Background: Within a single depressive episode, most patients receive different antidepressants because of an inadequate response to the first-line antidepressant. A commonly used strategy is to switch from a selective serotonin reuptake inhibitor to a selective serotonin-norepinephrine reuptake inhibitor. However, little is known about the tolerability of this switch with consideration of dose and drug concentration in blood. Methods: After 4 weeks of inadequate response to escitalopram (10–20 mg/d), medication was switched to another 4 weeks of venlafaxine (VF, 150–375 mg/d) in 234 depressed patients. Serum concentrations, depression severity, and adverse drug reactions (ADRs) were assessed weekly. Results: The switch of medication led to an increase of ADRs such as reduced salivation (+11%), orthostatic dizziness (+11%), and sweating (+9.8%). The most frequent ADRs during treatment with VF were reduced salivation (28.6%), sweating (24.6%), and orthostatic dizziness (15.8%). In patients receiving high-dose VF, a significant improvement of depressive symptomatology was observed, and most ADRs decreased during the course of treatment, even in patients above the therapeutic reference range. Limitations: Patients and physicians were aware of medication, and there was no direct comparison with the herein presented switch of medication. Implications: This study provides important information about the tolerability of a commonly used antidepressant treatment strategy. More detailed information about putative ADRs may help clinicians increase compliance through effective patient education. Because ADRs of VF were associated with the plasma concentration, therapeutic drug monitoring is recommended to guide the therapy and manage problems of tolerability. Abstract : Supplemental digital content is available in the text.